Broadening the tax base: a case for the informal real estate sector in Zambia - Siame, Chilengwe George (Rhodes University, Faculty of Commerce, Rhodes Business School, 2010)
The main objective of the study was to analyze the potential tax collection from the informal rental housing market in Zambia, using household level rental housing data collected for the Lusaka Urban District by the Central Statistical Office (CSO) as a basis for computation and extrapolation to the national level. This data was used to analyze household monthly expenditure on housing (rent), the total number of households in rented accommodation, and the tax regime applicable on rental income, to estimate the potential tax revenue that could be realized from this emerging sector. The estimates indicate that about K9.7 billion revenue could be collected on income from rental housing in Lusaka Urban District alone and a total of K83 billion nationally per annum. This represents about 0.4 percent of the country's GDP in 2007. Compliance needs to be improved and legislation revised to ensure that the landlords are compelled to remit tax to the Zambia Revenue Authority. The current legislation makes enforcement and compliance difficult as it places the statutory tax burden on tenants, who are very mobile. It is, therefore, recommended that the landlord is made responsible for the payment of taxes due on rental income and that any compliance requirements be enforced against the real estate/property that is generating the income. This study also examines the performance of the presumptive taxation regime in Zambia The study uses data from the Zambia Revenue Authority on revenue collection from presumptive taxes which were introduced to capture income from the informal sectors. The presumptive taxes already introduced in Zambia include: base tax, advance income tax and turnover tax for minibuses and taxi operators. To analyze the performance of the presumptive tax regime, the study utilizes data on imports made by those not registered for taxes, to estimate how much revenue could be generated by imposing a 3 percent turnover tax on the value of their imports at importation. The analysis shows that the Zambia Revenue Authority increased revenue collection from K5.3 billion in 2004 to K33.5 billion in 2007. This improvement in revenue collection is far below the potential, however, which is estimated at over K501 billion on imports of unregistered traders alone. To collect this revenue and expand the tax base, the tax authority needs to improve the administration of advance income tax on unregistered importers, and raise the advance income tax rate to a level where the importer is indifferent between paying the advance tax at the border and paying turnover tax inland.
Keywords: Real property and taxation -- Zambia; Tax administration and procedure -- Zambia; Rental housing -- Taxation -- Law and legislation -- Zambia; Informal sector (Economics) -- Taxation -- Law and legislation -- Zambia